EVALUATION OF THERMAL REQUIREMENTS AND LIFE OF DISTRIBUTION TRANSFORMERS IN REGIME NON-SINUSOIDAL PERIODIC: n/a (ELECTRICAL MACHINES, MATERIALS AND DRIVES — PRESENT AND TRENDS, 2021)
Electric transformers are some of the most important equipment in the entire electricity distribution chain. Their operation with optimal values ​​of the parameters (electrical, thermal, and mechanical) ensures the continuous supply of consumers, but also a corresponding quality of electricity supplied to them. The modern electrical loads that transformers power are often nonlinear and generate several problems with the quality of the energy in the grid, especially the distortion of the waveform of the current that flows through the windings of the transformer. This generates additional stresses (electrical and thermal) of the various components of the transformer (originally designed to operate in pure sinusoidal mode), which can cause abnormal (malfunctioning) operation of the transformer, ultimately reducing its life ( estimated by the manufacturer for the permanent sinusoidal regime). To prevent or diminish the negative effects of the deforming regime on the transformer, a deliberate limitation (reduction) of its maximum load is achieved. The procedure is known as transformer naming or derating. The aim is to establish the most appropriate declassification factors (denomination), resulting from the correlation of the nominal and constructive data of the transformer with the energy quality parameters, measured in its secondary (usually, these are the distortion level of the currents and their harmonic spectrum ). This paper analyzes qualitatively and quantitatively these issues and proposes a downgrading procedure for transformers inexploitation that illustrates a case study.
Keywords: Distribution electrical transformers; Thermal stresses; Periodic non-sinusoidal regime